Treatment of Oral Submucous Fibrosis: A Case Report - Zhao, Min (Archives of Clinical and Medical Case Reports, 2022)
Background: Oral submucous fibrosis (OSF) is a progressive and inflammatory mucosal fibrosis disease with cancerous tendency. Even though the exact etiology and pathogenesis of OSF have not yet been elucidated totally, the currently recognized pathogenic factor is areca nut. The typical symptoms of OSF patients with limited mouth opening directly affect life quality. Treatments focus on reducing inflammation and improving mouth opening to improve a patient’s quality of life. Steroids and corticosteroids are used to treat OSF for a long time because of preventing inflammatory response, reducing fibroblast proliferation, and alleviating collagen deposition. It was also reported that Chinese medicine formulas such as salvia/miltiorrhiza have certain effects in OSF treatment by means of activating blood circulation, removing blood stasis and softening the stiffen oral mucosa. Case Presentation: This case report describes the patient with limited month opening and the 3 years history of chewing areca nuts. The diagnosis of oral submucous fibrosis was confirmed with histopathological examination. With the combined treatment of sublingual compound Danshen dropping pills and topical triamcinolone acetonide for mouth rinse, the patient achieved curative effects of obviously improved mouth opening and soften oral mucosa. And the mechanism of the treatment was discussed. Conclusions: The combined treatment of topical triamcinolone acetonide and sublingual compound Danshen dropping pills may get good effects for OSF patients but need further study.